CubeSat Communication Subsystems: A Review of On-Board Transceiver Architectures, Protocols, and Performance - Amr Zeedan (17983750) (2023)
Small satellite communications recently entered a period of massive interest driven by the uprising commercial and civil space applications and motivated by various technological advances. Miniaturized satellites, known as CubeSats, are particularly attractive due to their low development and deployment costs which makes them very promising in playing a central role in the global wireless communication sector with numerous applications ranging from Earth imaging and space exploration to military applications. Moreover, constellations of CubeSats in low Earth orbits (LEOs) can meet the increasing demands of global-coverage low-cost high-speed flexible connectivity. However, this requires innovative solutions to overcome the significant challenges facing high-data-rate low-power space communications. This paper provides a comprehensive review of the design, protocols, and architectures of state-of-the-art CubeSat communication subsystems with a particular focus on their baseband structures. The literature is surveyed in detail to identify all design, testing, and demonstration stages as well as accurately describe the systems’ architectures and communication protocols. The reliability, performance, data rate, and power consumption of the reviewed systems are critically compared and evaluated to understand the limitations of existing CubeSat transceivers and identify directions of future developments. It is concluded that CubeSat communication subsystems still face many challenges, namely the development of energy-efficient high-speed transceivers that satisfy CubeSats’ cost, mass, size, and power constraints. Nevertheless, several directions for improvements are proposed such as the use of improved channel coding algorithms, Field Programmable Gate Arrays (FPGAs), beamforming, advanced antennas, deployable solar panels, and transition to higher frequency bands. By providing a concrete summary of existing CubeSat on-board transceiver designs and critically evaluating their unique features and limitations as well as offering insights about potential improvements, the review should aid CubeSat developers, researchers, and companies to develop more efficient high data rate CubeSat transceivers. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3304419